Human Development Index and Labor Productivity in Central Sulawesi Province: Granger Causality Test and Panel Data Regression - Suparman Suparman; Wahyuningsih Wahyuningsih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect of the human development index (HDI) on labor productivity. This study used panel data by district/city in Central Sulawesi Province in 2017-2020. The analytical method used is the Granger Causality Test and the panel data regression model. This study found that first labor Productivity (LP) had a positive and significant effect on the productivity index (PI). Second is the open unemployment rate (OUR) has a positive and significant effect on the human development index (HDI). Third, the open unemployment rate (OUR) has a negative and significant effect on the labor force participation rate (LFPR).